Does a reduced glucose intake prevent hyperglycemia in children early after cardiac surgery? a randomized controlled crossover study - de Betue, Carlijn TI (BioMed Central, 2012)
INTRODUCTION: Hyperglycemia in children after cardiac surgery can be treated with intensive insulin therapy, but hypoglycemia is a potential serious side effect. The aim of this study was to investigate the effects of reducing glucose intake below standard intakes to prevent hyperglycemia, on blood glucose concentrations, glucose kinetics and protein catabolism in children after cardiac surgery with cardiopulmonary bypass (CPB). METHODS: Subjects received a 4-hour low glucose (LG; 2.5 mg/kg per minute) and a 4-hour standard glucose (SG; 5.0 mg/kg per minute) infusion in a randomized blinded crossover setting. Simultaneously, an 8-hour stable isotope tracer protocol was conducted to determine glucose and leucine kinetics. Data are presented as mean ± SD or median (IQR); comparison was made by paired samples t test. RESULTS: Eleven subjects (age 5.1 (20.2) months) were studied 9.5 ± 1.9 hours post-cardiac surgery. Blood glucose concentrations were lower during LG than SG (LG 7.3 ± 0.7 vs. SG 9.3 ± 1.8 mmol/L; P < 0.01), although the glycemic target (4.0-6.0 mmol/L) was not achieved. No hypoglycemic events occurred. Endogenous glucose production was higher during LG than SG (LG 2.9 ± 0.8 vs. SG 1.5 ± 1.1 mg/kg per minute; P = 0.02), due to increased glycogenolysis (LG 1.0 ± 0.6 vs. SG 0.0 ± 1.0 mg/kg per minute; P < 0.05). Leucine balance, indicating protein balance, was negative but not affected by glucose intake (LG -54.8 ± 14.6 vs. SG -58.8 ± 16.7 μmol/kg per hour; P = 0.57). CONCLUSIONS: Currently recommended glucose intakes aggravated hyperglycemia in children early after cardiac surgery with CPB. Reduced glucose intake decreased blood glucose concentrations without causing hypoglycemia or affecting protein catabolism, but increased glycogenolysis. TRIAL REGISTRATION: Dutch trial register NTR2079.